1997
DOI: 10.1002/jlb.61.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive retroviral peptides: Immunopathological implications for immunosuppressive influences of retroviral infections

Abstract: Abstract:Studies ofthe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 105 publications
0
43
0
1
Order By: Relevance
“…Previously we and others have reported that CKS-17 primarily down-regulates Th1-type immune response, including inhibition of IL-12 production (reviewed in Ref. 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously we and others have reported that CKS-17 primarily down-regulates Th1-type immune response, including inhibition of IL-12 production (reviewed in Ref. 8).…”
Section: Discussionmentioning
confidence: 99%
“…One highly conserved region of the transmembrane proteins contains a leucine zipper-like domain comprising an ␣ helical secondary structure that may play an important role in the processes of virus fusion, infectivity, and entry (4 -7). Of interest, this leucine zipper-like domain overlaps a unique region that has strong immunosuppressive potential (5,7,8). CKS-17, a synthetic peptide, represents the prototypic amino acid sequence of this immunosuppressive domain (9) and has been found to exhibit potent immunosuppressive activities in numerous immune reactions both in vitro and in vivo (reviewed in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The endogenous MuLV envelope protein may retard the immune aggression to cells rather than accelerating the onset of IDDM. Since the same amino acid sequences suppressing the cellular immunity were located in our MuLV envelope protein [41,42], our endogenous MuLV envelope protein would reduce the cellular immunity against cell [29]. In fact, the long duration of insulitic stage before onset of IDDM and high expression of MuLV envelope gene during this stage suggests the existence of immune suppression.…”
Section: Discussionmentioning
confidence: 98%
“…However, more elaborate CTL analysis using MIN6N8a-primed CD8+ T cell isolated from draining lymph nodes should be carried out before getting a conclusion that MuLV envelope protein is not an autoantigen involved in the pathogenesis of NOD mouse IDDM. Since it was reported that retroviral envelope protein had the immune suppressive activity [29], our recombinant 3-2 envelope protein possibly downregulates the capability for cellular proliferation of NOD T cell in T cell proliferation assay.…”
Section: Discussionmentioning
confidence: 99%